SISTEM ADMINISTRASI KREDIT MIKRO DALAM MENUNJANG OPERASIONAL PERBANKAN DI PT BANK RAKYAT INDONESIA (PERSERO) TBK CABANG PALANGKA RAYA - Putri Soraya; Berta Margareta Agustin Wijaya (Yayasan Nusa Cendekia Global, 2026)
This community service program, implemented through the Independent Impact Internship, aims to analyze and systematically improve the role of micro-credit administration systems in supporting operational efficiency at PT Bank Rakyat Indonesia (Persero) Tbk Palangka Raya Branch Office. The focus of the intervention encompasses physical records management, continuous document scanning into the BRImen system, processing the UM06 authorization forms, and resolving administrative bottlenecks in micro-credit distribution (such as KUR and Kupedes). This activity adopts a descriptive qualitative approach utilizing a Participatory Action Research (PAR) design. Primary data was obtained through direct daily involvement, in-depth observation, and structured logbook records from January 22 to May 26, 2026. The results demonstrate that orderly administration in the back-office unit acts as the main determinant of service speed and excellence at the front-office. The implementation of dual safety measures digitizing collateral files into the BRImen cloud and physically organizing them in fireproof vaults has proven highly effective in accelerating information retrieval, minimizing human errors, and ensuring document security. However, the evaluation highlights that the high volume of daily micro-credit applications, manual authorization processes requiring wet signatures, and incomplete customer documents (such as missing SPH) remain operational obstacles that frequently delay service. Therefore, standardizing daily wrap-up document scanning, enforcing strict document cross-checks at the front-end, and advocating for the adoption of digital signatures are crucial solutions to accelerate micro-credit disbursement and elevate the overall quality of banking services.